Effects of Deep Fluids on Middle Permian Dolomite of the Western Sichuan Basin - Huang, Huiwen; Chen, Hongde; Huo, Fei; Yang, Shuai; Chen, Anqing (Frontiers in Earth Science, 2022)
Deep fluid activity is closely related to carbonate reservoir transformation as well as oil and gas accumulation. The large-scale deep fluid activity caused by Emeishan Large Igneous Province (ELIP) brought a lot of deep material and energy to Sichuan Basin, changed the paleogeothermal and geochemical field of the region they flowed through, which had an important impact on the formation of Middle Permian dolomite reservoir in Western Sichuan. Through comprehensive analyses of petrographic, geochemical and fluid inclusion data from two drill core and three outcrop sections of the Middle Permian Formation in the western Sichuan Basin, the dolomitizing fluid, dolomite genesis and affect of deep fluid were discussed. The dolomite were divided into four types which are matrix dolomites (Md1, Md2 and Md3) and cement dolomites (Cd). Among them, the Md1 were formed in penecontemporaneous seawater by seepage reflux dolomitization, while Md2 were formed in heated Permian seawater through thermal convection. In the northwest of study area, the Md3 and Cd were formed by higher-temperature thermal convection without hydrothermal.In the southwest of study area, the lower δ13C value and Sr contents, higher Mn contents and 87Sr/86Sr ratios, positive Eu anomalies as well as much higher Th and salinity values of inclusions shows that hydrothermal participated in the dolomitization, forming the Md3 and Cd through structure-hydrothermal dolomitization and the thermal convection of seawater mixed with hydrothermal. The deep fluid activities of ELIP provided both the material source (Mg2+) for the dolomitization process and the migration motive power for the dolomitization fluid. From the southwest to northwest, with the deep fluid activity decreasing, the abundance of Md3 and Cd which are closely related to the hydrothermal solution reduced.